Strategic Insights to Enhance Student Loyalty Through Service Quality and Satisfaction: Importance-Performance Map Analysis - Luthfiana, Yusrina; Sujarwoto, Sujarwoto; Said, Moh. (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
The increasing competition among higher education institutions (HEIs) has driven them to enhance their competitive advantage by fostering student loyalty. When students perceive high service quality, they are more likely to feel valued and remain loyal. This study employs Importance-Performance Map Analysis (IPMA) to identify key areas for improvement in higher education service quality and student satisfaction to enhance student loyalty. The sampling technique used was proportionate stratified random sampling of the students of Faculty of Engineering, Universitas Negeri Jakarta per study program. The IPMA results, based on survey data from students, highlights service quality as the primary area requiring improvement. At the indicator level, seven keys are identified, including student skill development, infrastructure, safety, employment quality, management and staff support, teacher’s profile, and satisfaction with university choice. These findings provide strategic insights for HEIs to enhance student loyalty by prioritizing service quality improvements. Future study could extend the analysis to multiple HEIs for boarder insights.